Exploring Whistleblowing Intention: The Interplay of Social Norms, Moral Intensity, and Professional Commitment among Auditors - Rafrini Amyulianthy; Khalida Utami; Aura Rahdiatul Rafidah; Fazlida Mohd Razali (Innovation Business Management and Accounting Journal, 2026)
Whistleblowing plays a vital role in uncovering organizational misconduct, but its success depends on individuals' willingness to report wrongdoing. Using the Theory of Planned Behavior, this study examines how subjective norms and moral intensity affect the intention to whistleblow, with perceived professional commitment acting as a mediating factor. The research focuses on internal auditors in Jakarta, Indonesia, a region facing ethical challenges and increased regulatory oversight. Data from 86 respondents from government inspectorates and multinational firms were analyzed with PLS-SEM in SmartPLS 4.0. The results show that subjective norms and moral intensity do not directly affect whistleblowing intention. Instead, perceived professional commitment has a strong, significant influence, fully mediating the effects of the other variables on whistleblowing intention. These findings emphasize the importance of internalized professional values in guiding ethical behavior, indicating that social and moral influences are channeled through professional identity, leading to ethical actions. The study expands the Theory of Planned Behavior by including professional commitment as a key psychological factor. Practical recommendations include developing ethics programs that reinforce professional identity and aligning organizational structures with ethical standards. Enhancing ethical commitment among auditors can promote greater transparency and integrity in organizations.